(untitled) (Scripta : English Department Journal, 2023)
This research aims to determine the effectiveness of the peer-feedback technique through Padlet in teaching writing recount text to the tenth-grade students of SMK Darul Ulum Kepuhdoko Jombang. This research employed quantitative experimental research. The data were gathered through tests, pre-test and post-test. The test did for measuring students’ achievement in recount text writing between the experimental class and the control class. The objective of the post-test was to find out the effect of peer-feedback techniques on students’ recount text writing. The data was analyzed by using t-test with 0.05 level of significant. The result shows that peer-feedback through Padlet give a positive effect on improving students’ recount text writing scores. The mean score of experimental group was 79.72 and for control group was 66.79, and the result of calculation t-value is 2.317, while the degree of freedom 44, the t-table is 2.015. t-value > t-table. It meant that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. It was concluded that using Padlet in peer-feedback to teach writing recount texts is effective and provides positive results.